A 21st Century View of the March 1989 Magnetic Storm. Issue 10 (23rd October 2019) - Boteler, D. H.
Abstract: On 13 March 1989, the largest magnetic storm of the last century caused widespread effects on power systems including a blackout of the Hydro‐Québec system. Since then this event has become the archetypal disturbance for examining the geomagnetic hazard to power systems. However, even 30 years on from 1989, the story of exactly what happened in March 1989 is far from complete. This paper reexamines the information available about the March 1989 event and uses this to construct a timeline and description of the space weather phenomena and how they caused the power system effects. The evidence shows that the disturbance was caused by two coronal mass ejections (CMEs): the first associated with a X4.5 flare on 10 March and the second linked to a M7.3 flare on 12 March. The arrival of the interplanetary CME shock fronts caused storm sudden commencements at 01.27 and 07.43 UT on 13 March. The transit time and speed of the first (second) interplanetary CME shock are 54.5 hr (31.5 hr) and 760 km/s (1, 320 km/s). Empirical relations are used to estimate solar wind speed and southward interplanetary magnetic field, Bs, and give values of v = 980 km/s, Bs = 40 to 60 nT at the peak of the storm. Key findings are that the second storm sudden commencement occurred at the same time as the substorm that impacted the Hydro‐Québec system and indicates that external triggering of the substorm may have contributed to a faster substorm onset than might otherwise have occurred. This caused the production of larger geomagnetically induced currents that caused the Hydro‐Québec blackout. The March 1989 storm had the largest recorded value of the Dst index representing the size of the magnetic storm main phase, but the Hydro‐Québec blackout occurred early in the storm when the Dst value was less disturbed. Only later in the storm did Dst reach its peak value. At this time an expansion of the auroral oval brought disturbances to lower latitudes where they caused power system problems in the United States, United Kingdom, and Sweden. Key Points: The extreme space weather conditions in March 1989 were the result of successive CMEs A secondary CME (resulting from a less intense flare) was the "trigger" for the extreme event The Hydro‐Québec system collapse occurred well before Dst reached its extreme value